2017
DOI: 10.1111/all.13320
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atopic dermatitis beyond childhood: A systematic review and meta‐analysis of longitudinal studies

Abstract: Background There are sparse and conflicting data regarding the long-term clinical course of atopic dermatitis (AD). Although often described as a childhood disease, newer population-based estimates suggest the prevalence of pediatric and adult disease may be similar. Methods Our objective was to determine whether there is a decline in the prevalence of AD in population-based cohorts of patients followed longitudinally beyond childhood. We conducted a systematic review and meta-analysis including studies asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
149
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(162 citation statements)
references
References 32 publications
9
149
0
4
Order By: Relevance
“…Our observation is in line with recent longitudinal assessments of AD, one of more selected patients and one meta‐analysing prevalence data at different ages . Thus, the prospective US PEER cohort study, enrolling 2‐17‐year‐olds with mild‐to‐moderate AD and TCI use, found that it was not until age 20 years that 50% of these patients had at least 1 lifetime 6‐month symptom‐ and treatment‐free period .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our observation is in line with recent longitudinal assessments of AD, one of more selected patients and one meta‐analysing prevalence data at different ages . Thus, the prospective US PEER cohort study, enrolling 2‐17‐year‐olds with mild‐to‐moderate AD and TCI use, found that it was not until age 20 years that 50% of these patients had at least 1 lifetime 6‐month symptom‐ and treatment‐free period .…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies confirm that it is difficult to study AD persistence properly since the disease is heterogeneous and recurrent. Accordingly, another meta‐analysis showed that the prevalence of AD decreased by as little as 1% after 12 years of age . In continuation, there is an emerging paradigm of AD being a lifelong, genetic predisposition to episodic skin lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The high rates of persistence in NHS2 are consistent with other recent studies. For example, a cohort study of children with mild‐to‐moderate AD found that 80% of participants still had periods of active disease into early adulthood and a systematic review found that there was no statistically significant drop year‐on‐year in the prevalence of AD within cohort studies …”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is increasingly recognized to persist into adulthood . This has spurred epidemiologic studies of adults with AD, including investigations of risk factors for development of AD and non‐atopic comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Atopic dermatitis (AD) is a common chronic pruritic skin condition in adults, characterized by skin barrier impairment, a T‐helper (Th) cell 2 skewed immune response and Staphylococcus aureus colonization . There is a little insight in the natural course of AD during pregnancy, and in particular the use of dermatologic therapy .…”
Section: Introductionmentioning
confidence: 99%